Asymmetric Information, Disagreement, and the Valuation of Debt and Equity - Banerjee, Snehal,Breon-Drish, Bradyn M.,Smith, Kevin (SSRN, 2022)
We study the prices of a firm's debt and equity in a market where investors have private information and may exhibit differences of opinion. We show how debt and equity valuations, and the impact of public information and distress risk on these valuations, depend upon disagreement and the intensity of liquidity trading. Moreover, debt and equity prices exhibit drift and reversals in response to news, the strength of which depend upon the firm's leverage. Finally, the firm's capital structure can influence its valuation, and the optimal capital structure depends on the relative amount of liquidity trade in debt versus equity
10.2139/ssrn.4278165
Keywords: Arbeitspapier; Graue Literatur; capital structure; rational expectations; difference of opinions; disagreement; liquidity trading; information quality